Idiopathic scrotal calcinosis: A case series - Sainath K Andola; Shabnam Karangadan; Suresh Patil (Wolters Kluwer Medknow Publications, 2014)
Idiopathic calcinosis of the scrotum is a rare benign local condition, characterized by multiple, painless, hard scrotal nodules, in the absence of any systemic metabolic disorder. We report nine cases of this rare entity diagnosed over a five-year period (2009-2013). The patients' age ranged from 26 to 65 years (Mean 42 years). The majority presented with scrotal swellings (8/9) and were clinically diagnosed as sebaceous cysts (7/9). Two cases also gave history of white chalky discharge from the swelling. Associated features of right inguinal hernia and left hematocele were seen in two cases. Five cases presented with a solitary nodule, with the size ranging from 0.5 to 3 cm (Mean 1.89 cm). The histopathological examination revealed dermal calcified masses with prominent foreign body reaction. All cases underwent surgical excision and showed no recurrence in follow up. This case series attempts to create an awareness of this rare pathology, which has an obscure pathogenesis and is often misdiagnosed.